2022
DOI: 10.1136/bcr-2022-251977
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella invasive syndrome: a challenging diagnosis

Abstract: Klebsiella invasive syndrome is a rare condition that typically presents as a liver abscess with metastatic infection, with mortality rates as high as 14% potentially due to diagnostic delay by clinicians. Here, we present a case of a woman in her 60s, who presented with symptoms and signs consistent with meningitis, imaging findings suggestive of possible leptomeningeal carcinomatosis a long with areas of lung consolidation and abdominal nodules and lymphadenopathy, presumably metastatic malignancy. We diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Several other studies of PLA patients also found that a positive blood culture was an independent risk factor for primary treatment failure [ 11 , 29 ]. It is likely that PLA patients with concomitant bloodstream infections have greatly weakened immunity, a condition that can aggravate PLA and possibly lead to invasive liver abscess syndrome, with infections of other organ systems, including meningitis, endophthalmitis, necrotizing fasciitis, and lung abscess [ 30 , 31 ]. The strain of KP responsible for PLA may also affect primary treatment failure [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies of PLA patients also found that a positive blood culture was an independent risk factor for primary treatment failure [ 11 , 29 ]. It is likely that PLA patients with concomitant bloodstream infections have greatly weakened immunity, a condition that can aggravate PLA and possibly lead to invasive liver abscess syndrome, with infections of other organ systems, including meningitis, endophthalmitis, necrotizing fasciitis, and lung abscess [ 30 , 31 ]. The strain of KP responsible for PLA may also affect primary treatment failure [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and lesion detection can reduce mortality. 5 Imaging of isolated liver abscess lesions in 18 F-FDG PET/CT has been reported in the past. [6][7][8] Increased 68 Ga-FAPI activity has been previously reported in different infectious diseases including syphilis, 9 organizing pneumonia, 10 tuberculosis, 11 and cryptococcus.…”
mentioning
confidence: 99%
“…So, it is easy to miss early identification. Early diagnosis and lesion detection can reduce mortality 5 . Imaging of isolated liver abscess lesions in 18 F-FDG PET/CT has been reported in the past 6–8 .…”
mentioning
confidence: 99%